1994
DOI: 10.1055/s-2008-1066075
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Sensitization to Latex in Children with Spina Bifida

Abstract: The risk of per-operative anaphylactic shock in response to latex is established in children with spina bifida. This study focuses on 30 children with spina bifida and aims at evaluating the value of predictive tests (skin tests and RAST). No patient had shown a preoperative accident. Hypersensitivity to latex, sometimes suspected by questioning of the patient, was detected 12 times out of 30 (40%). 10 children of the 12 were atopic (83%). The incidence of atopy is significantly higher than that of the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 2 publications
1
12
1
Order By: Relevance
“…This high percentage of latex sensitized children with spina bi®da is in accordance with the literature [2,4,7,16]. Antibody formation is promoted by the ®rst operation soon after birth and is stimulated by repeated operations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This high percentage of latex sensitized children with spina bi®da is in accordance with the literature [2,4,7,16]. Antibody formation is promoted by the ®rst operation soon after birth and is stimulated by repeated operations.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies showed a higher prevalence of atopic children among the latex sensitized patients with spina bi®da [4,7,15,16], in studies with greater numbers of patients ranging from 35% [7] to 49% [15]. We found 22% of children with atopic disease in our study without any signi®cant dierence between latex sensitized and not sensitized children.…”
Section: Discussioncontrasting
confidence: 43%
“…We found a rate of sensitization to latex of 49% in the spina bifida group. In the literature, prevalence rates range from 34% [8], 40% [9] and 49% [10] up to 64.5% [11]. The validity of our data may be high, because we investigated the largest number of spina bifida patients published so far.…”
Section: Sensitization To Latexmentioning
confidence: 94%
“…We found that 34% of latex-sensitized patients with spina bitida were atopic in terms of presence of specific IgE in serum to common environmental allergens. In the literature, figures from 27% [2] up to 83% [9] have been reported. However, the numbers of patients were small in these studies.…”
Section: Atopic Dispositionmentioning
confidence: 99%
“…By far the most relevant risk group are children with spina bifida: prevalence rates for sensitization in these children range from 25 [14], 34 [15], 38 [16], 40 [17], 49 [18], and 55.3 [19]to even 64.5% [20]. In summary, approximately every second child with spina bifida is sensitized to latex.…”
Section: Epidemiologymentioning
confidence: 99%